Legal analysis of the implementation of article 33 of the criminal code concerning minors in military relations with law number 11 of 2012 concerning the juvenile criminal justice system - Hidayat, Wahyudi (Dynamics of Politics and Democracy, 2024)
Purpose: This study aims to analyze the legal protection of children in conflict with the law within the Indonesian criminal justice system, particularly military minors. Article 33 of the Criminal Code and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System are both central in regulating the judicial process for minors in military service. However, the potential contradiction between these two legal frameworks requires critical examination to ensure that children's rights are not violated. Research/methodology: This research uses a normative juridical approach. Data were collected through document analysis and literature study, including library research and other sources related to juvenile justice and military law. Results: The study finds that although both Article 33 of the Criminal Code and Law Number 11 of 2012 are designed to provide protection, their implementation in cases involving military minors may lead to legal uncertainty. There is a need for legal harmonization to uphold fair trial principles and to ensure that military minors are given the same special protections as other children in conflict with the law. Conclusion: Legal inconsistencies can negatively affect the rights of military minors. Reconciliation between general criminal law and juvenile justice law is necessary to create a more just legal framework. Limitation: This study is limited to legal analysis and does not involve empirical case data or interviews with practitioners. Contribution: The study contributes to legal scholarship by highlighting the urgency of synchronizing juvenile justice with military regulations, ensuring fair legal treatment for all minors.